2023
DOI: 10.1177/00375497231152458
|View full text |Cite
|
Sign up to set email alerts
|

A methodological approach for modeling the spread of disease using geographical discrete-event spatial models

Abstract: The study of infectious disease models has become increasingly important during the COVID-19 pandemic. The forecasting of disease spread using mathematical models has become a common practice by public health authorities, assisting in creating policies to combat the spread of the virus. Common approaches to the modeling of infectious diseases include compartmental differential equations and cellular automata, both of which do not describe the spatial dynamics of disease spread over unique geographical regions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…While the focus of this study is on the EVCI location problem, it is worth noting that the GIS-based simulation methods have found utility in other disciplines. For instance, Davidson et al 48 developed a discrete-event spatial model to simulate disease spread within a pandemic, demonstrating its adaptability and ability to provide deterministic predictions for multiple regions simultaneously. Other studies using simulation to investigate the spread of infectious diseases can be found in the work by Abadeer et al, 49 as well as the review article by Ayadi et al 50 Iskandar et al 51 developed an agent-based model that incorporates realistic human behavior and urban conditions to simulate pedestrian evacuation during earthquakes at the city scale, revealing the impact of debris and human behavior on population safety and the limited capacity of open spaces to provide shelters in Beirut, Lebanon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the focus of this study is on the EVCI location problem, it is worth noting that the GIS-based simulation methods have found utility in other disciplines. For instance, Davidson et al 48 developed a discrete-event spatial model to simulate disease spread within a pandemic, demonstrating its adaptability and ability to provide deterministic predictions for multiple regions simultaneously. Other studies using simulation to investigate the spread of infectious diseases can be found in the work by Abadeer et al, 49 as well as the review article by Ayadi et al 50 Iskandar et al 51 developed an agent-based model that incorporates realistic human behavior and urban conditions to simulate pedestrian evacuation during earthquakes at the city scale, revealing the impact of debris and human behavior on population safety and the limited capacity of open spaces to provide shelters in Beirut, Lebanon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While these models have become quite sophisticated over the years and advanced techniques have been applied to optimize the SEIR parameters (e.g., via swarm optimization 1 ), they mostly rely on assumptions such as homogeneity of the individuals in a population and the distinction of agents solely based on their disease state, that limit the accuracy of the predictions that can be made. [2][3][4][5] In the real world, however, the spread of a disease is not only affected by the properties of the virus itself, but also by sociopsychological behavioral dynamics that heavily rely on aspects that are heterogeneous across individuals (including spatial and demographic heterogeneity 6 ). Squazzoni et al 7 point out that, given the significant adverse effects that behavioral interventions can have on individuals, decisions ''cannot be solely based on epidemiological knowledge, because the efficacy of implementation depends on people's reactions, pre-existing social norms, and structural societal constraints.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the authors present a SEAIRD model that showed a similar transition method as those described previously. They use an asymptomatic state where an asymptomatic rate α is defined to split the infected population into infectious or asymptomatic.…”
Section: Asymptomatic Diseases and Seaird Modelsmentioning
confidence: 99%
“…Our implementation allows users to run the model at a user-defined region level and visualize how a disease might spread through a city, town, or country. The model is designed using the Cell-DEVS formalism [12] and implemented using the Cadmium simulator [13]. The model's adaptable framework allows for accessible rapid-prototyping and modifications.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%